The UAE Tour, cycling stars, and Twitter: Tweeting as part of promoting the host country - Zákravský Jiří (Sciendo, 2021)
Using the example of the 2019 inaugural UAE Tour, this study demonstrates how cycling stars indirectly promote countries hosting globally watched sporting events through their Twitter accounts. This study presents a qualitative and quantitative content analysis of the Twitter activity of selected cycling stars. However, this promotion is only a secondary result of their activity on social media; professional athletes use their Twitter accounts as a platform for self-presentation and to show their daily lives to fans. If the athletes are active on social media, it is almost impossible for them to avoid speaking about the host countries, indirectly evaluate them, and provide information about them to their followers. While sports celebrities' social media profiles are a limited space for the promotion of host countries, they can also help improve the image of the countries and present them in a positive light. Of course, political leaders use countless public or sports diplomacy tools to promote their countries abroad, and online platforms are not necessarily a key element in the promotion of their international image.